The Truce of Richmond and the End of First World War (1914-1918) - Ouarti Djamel (مجلة جامعة الأنبار للعلوم الإنسانية, 2021)
The present research paper is an attempt to shed some light on the causes of Germany’s ratification of the Armistice of Rethondes on November 11th, 1918 that ended fighting in World War I. The armistice was signed by the German civilian politician Matthias Erzberger and the Allied Supreme Commander, Marshall Ferdinand Foch in a railroad carriage at Compiègne forest. The paper will clarify the political and military developments during the last two years of the war between Germany and the Allies, mainly with the withdrawal of Bolshevik Russiaafter the Treaty of Brest-Litovsk on Marsh 3rd, 1918. The United States of America took part in the war by the side of the Allies in April 1917 after the American President Wilson’s fourteen principles had been outlined on January 14th, 1918 among which the right of people to self-determination. The upheaval of socialism as a new political and economic system brought many conceptual changes mainly in Germany and the end of the German Reich (1871-1918) due to a socialist revolution prior to the war supported by Rosa Luxemburg and Karl Liebknecht. Henceforth, came a republican government and signed f the armistice with the Allies first and then the Treaty of Versailles on June 28th, 1919. Indeed, the signature of the Armistice of Rethondes and the Treaty of Versailles nurtured the German nationalism between 1919 and 1939 paving the way to World War II and the ramification of a second Armistice of Rethondes by France, this time, on June 22nd, 1940 at Compiègne forest in the same railroad carriage where Germany, in 1918) signed the first armistice.